Demographic aspects of tick bites in Belgrade: two-year retrospective study - Zelenović, Aleksandra G; Minić, Snežana (Medicinski podmladak, 2018)
Introduction: Ticks are becoming an increasing problem in Europe. Every outing in nature bares a risk of a tick bite, especially in the spring and summer. Ticks are spiderlike ectoparasites from the Ixodida family, subclass Acarina. They may induce an irritation, trigger abscess and carry numerous spirohets, most commonly the bacteria Borrelia burgdorferi which can cause Lyme disease. The goal of this study was to determine the distribution of tick bites in studied population according to: bite localization, time (according to months) and Belgrade municipaliteies where the bite occurred. Material and methods: 1199 individuals participated in this retrospective study, who were being treated at Dermatovenerology Clinic KCS Belgrade between January 2014 and December 2015, for tick bites. Following data was gathered: demographic data, geographical data about the place where the bite occurred, time of year, as well as the part of the body that was influenced. Results: In the year 2014, 600 (50%) patients were treated, whereas in 2015 599 (50%) patients were treated. There were 715 (59.7%) males and 483 (40.3%) females. The average age of the participants was 41 (1-87). Most of the participants had one bite, 1128 (94.1%), 19 (1.6%) participants had two bites, while 6 (0.5%) participants had more than two bites. Most of the bites occurred during spring months 989 (82.5%), in the municipalities of Vozdovac 244 (20.4%) and Cukarica 224 (18.7%). The most common bite sites were below the waist line in all participant groups except for children, who had bites in the head and neck region. Conclusion: Exposure to ticks carries a risk of getting Lyme disease. Whether or not the tick may be infected, it is suggested to take it out as soon as possible, so that it would not feast on blood and influence Lyme disease. Key words: tick, Lyme disease, Borrelia burgdorferi, Belgrade municipalities